14=-5y+3(y-2)

Simple and best practice solution for 14=-5y+3(y-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14=-5y+3(y-2) equation:


Simplifying
14 = -5y + 3(y + -2)

Reorder the terms:
14 = -5y + 3(-2 + y)
14 = -5y + (-2 * 3 + y * 3)
14 = -5y + (-6 + 3y)

Reorder the terms:
14 = -6 + -5y + 3y

Combine like terms: -5y + 3y = -2y
14 = -6 + -2y

Solving
14 = -6 + -2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2y' to each side of the equation.
14 + 2y = -6 + -2y + 2y

Combine like terms: -2y + 2y = 0
14 + 2y = -6 + 0
14 + 2y = -6

Add '-14' to each side of the equation.
14 + -14 + 2y = -6 + -14

Combine like terms: 14 + -14 = 0
0 + 2y = -6 + -14
2y = -6 + -14

Combine like terms: -6 + -14 = -20
2y = -20

Divide each side by '2'.
y = -10

Simplifying
y = -10

See similar equations:

| 18y=-20+19y | | -17-4k=3k+13-5k | | 0=-7r-3r | | 3(2x+5)=-37+22 | | 29=8+3x | | 25(x^2)-20x+4=0 | | 3g+9=4g | | 10-7k=-(8k-7) | | 8-9z=-5z | | 5-3(X-4)=11 | | -8=6(v-4)-8v | | -34+4p=-7(8+p) | | 7x-44=10-5x | | 0=7+5x^2-2x^3 | | 5+6h=-5+5h | | 4/5t+1=t+1/2 | | -3j-4j-1=-3j+7 | | 34=-8y+6(y+8) | | 16=p-5p | | -10-2n=-n | | 8n=7n-3 | | y=x^6-7x | | 9d=9+10d | | 4x^2-35x-414= | | 3w+15=48 | | 10B+8=68 | | -5(r+4)=-72 | | 10-7r=8-9r | | 2.4k=18.96 | | 4x^2+35x-414= | | 10y-12=48 | | 5(x+6)-7x=26 |

Equations solver categories